New Studies of Locke Philosophy of Religion - Khelufi, Amina (Sententiae, 2017)
The author describes new interpretations of the problem of theology’s influence on John Locke’ philosophical doctrine. The main subject of the analysis is the latest publications by Victor Nuovo, the most famous contemporary researcher of mentioned problem.